Understanding the Dynamics of the Prices of Natural Gas as an Important Step in Energy Transition - Bech-Wysocka, Katarzyna (Journal of Public Governance, 2021)
Objectives: The natural gas seems to be an attractive supplement to the renewable energy sources in energy transition towards low carbon emissions. Given its flexibility to transmit and store, the natural gas offers a diversity of the renewables. Understanding the formation of natural gas prices is crucial for evaluating the costs of energy transition, in particular the return to investment into natural gas infrastructure. Research Design & Methods: In order to study the natural gas prices dynamics in Poland, I developed a Vector ErrorCorrection model (VECM) for a joint determination with prices in the USA and in Europe. The VECM setup made it possible to analyse the interactions among non-stationary prices as well as investigate how disturbances specific to the discussed markets pass on within the system. Findings: By exploring impulse response functions and forecast error variance decompositions, I demonstrate that the European natural gas prices are not affected by shocks in the American gas market, as they are determined solely by the shocks specific to the European natural gas market. Additionally, the natural gas prices in Poland are highly correlatedwith, and responsive to, other European countries’ prices. The results go in line with the hypothesis of the existence of a common, integrated European natural gas market. Implications / Recommendations: In the context of energy transition, the return to investment within natural gas infrastructure can only be forecast given the predicted prices. The appropriate proportion of alternative energy sources in the energy mix can be achieved only after examining this dynamics and the differences in prices of alternative energycommodities. Hence, the feasibility of predicting natural gas prices should always be considered at the early stages of any energy transition policy. Contribution / Value Added: The results add to the discussion on the role of natural gas in energy transition. They revealhow gas prices on the main markets have fluctuated over the recent years as well as they link the prices in Poland to natural gas prices abroad. The findings fill the gap in the literature, which so far has been focused mainly in the Americanmarket.